2017
DOI: 10.4103/0972-9941.181762
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of intra-abdominal bladder perforation in preschool children

Abstract: Intraperitoneal bladder rupture is uncommon in very young children, but its incidence may increase with increasing use of seat and lap belts. To the best of our knowledge, there are no prior reports of laparoscopic repair of this injury in children. We describe two recent cases and discuss useful technical points that facilitate a successful laparoscopic repair. Both our patients were preschool age girls who sustained seat and lap belt injuries. Contrast computed tomography scan suggested a large amount of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Review of the literature revealed only two reports involving four children who had laparoscopic repair of intraperitoneal bladder rupture. [ 5 6 ] However, all these children were aged 3 years and above and the mechanism of injury was RTA. Ours is the smallest reported child to have an intraperitoneal bladder rupture following the most unusual mode of injury and also to have a laparoscopic repair of the same.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature revealed only two reports involving four children who had laparoscopic repair of intraperitoneal bladder rupture. [ 5 6 ] However, all these children were aged 3 years and above and the mechanism of injury was RTA. Ours is the smallest reported child to have an intraperitoneal bladder rupture following the most unusual mode of injury and also to have a laparoscopic repair of the same.…”
Section: Discussionmentioning
confidence: 99%